Screening of algae collected from Nha Trang bay, Vietnam, for potential cosmeceutical bioproducts - Hoang, Kim Chi; Tran, Thi Hong Ha; Truong, Ngoc Hung; Tran, Thi Nhu Hang; Tran, Thi Hong Tham; Le, Mai Huong; Le, Huu Cuong (Vietnam Journal of Marine Science and Technology, 2022)
As marine seaweeds are a great source of natural products, investigating biological properties for appropriate management and exploitation is a priority. For our study, we collected and extracted indigenous algal samples from marine areas of Nha Trang bay belonging to nine species of Chlorophyta, Rhodophyta, and Ochophyta to investigate their cosmeceutical activities. Results revealed tyrosinase inhibitory activity of methanolic extracts of Halimeda sp. and Ulva lactuca with 57.17 ± 1.70% and 54.32 ± 0.52% of inhibition, respectively. Additionally, methanolic extracts of U. lactuca, Sargassum mcclurei, and S. aquifolium were found to perform moderate scavenging capacity against DPPH free radicals. By the colorimetric method, the algae extracts were determined to exhibit no potent cytotoxic effect on both fibroblast cell line NIH-3T3 and keratinocyte cell line HaCaT at a test concentration of 20 µg/mL and thus considered promising for further safety evaluation. The investigation provides information on biological activities of our marine algae and highlights candidates with application significance.